Factors Affecting Tardiness of Part-Time Medical Specialists at the Polyclinic of X Hospital (Universitas Negeri Semarang, 2021)
Service waiting time in an outpatient is an indicator of minimum hospital quality service standards. The amount of waiting time at the X hospital's polyclinic in 2018 was 84.75 minutes, exceeding the hospital quality service standard in 2009 at 60 minutes. The preliminary research shows that the waiting time for medical services by part-time medical specialists was 60.75 minutes. This study aims to identify factors that affect part-time medical specialists' tardiness at X Hospital's polyclinic. This study performed an analytical survey using a cross-sectional approach from May to June 2020. It collected data from 67 part-time medical specialists who conduct medical practices at the polyclinic. Univariate, bivariate Spearman correlation and multivariate multiple linear regression tests with the Backward method were performed to analyze data. The bivariate analysis shows a significant effect of biographical characteristics factor where practice hours are less the standard time of 60 minutes ( p=0.01) and extrinsic factor of the work environment (p= 0.019) on the tardiness of part-time medical specialists. Work environment was the most affecting factor in late medical practices (p=0.016, Exp B/OR -0.433). This study could be a reference for the hospital to manage the human resources in terms of proper practice hours and a supportive work environment for patient medical services.